Community-Based Development and Collective Learning: How Does a Local Community Engage and Learn to Initiate a Smart Village Development? - Adi Suryani; Soedarso Soedarso (Journal of Development Research, 2021)
The aim of this study is examining learning process undertaken by Klagen, Nganjuk local community in their journey to transform their rural area into a smart village ad what they need to promote their collective learning. The data are collected through two main methods: community dialogue and direct participant observations during village visits and business training, particularly for Klagen’s youth. Thematic analysis, which is grounded on empowerment steps, is performed to interpret the gathered data. Many previous studies examine the outcome of smart village, as the end product. Differently, this study aims to explore the process to develop a smart village, especially at the initial stage and presents development-community education interfaces. The study indicates that to transform their village into a smart village, Klagen community should collaboratively engage in community sharing in which they build shared vision to change, integrate ideas, thinking and social-cultural analysis, observational learning in which they learn from neighbor village model, partnership seeking in which they explore potential networking outside their village area and business-entrepreneurship learning in which the young people learn how to initiate and manage local business.